Analysis and Design Improvement of the XYZ Coffee App Using a User-Centered Design Approach - Astawan, Putu Bagus Rangga Permana Putra; Wirawan, I Made Widhi; Suhartana, I Ketut Gede; Astuti, Luh Gede (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2025)
XYZ Coffee App is a website designed to provide people informations about XYZ Coffee, including its menu. However, usability testing using the System Usability Scale (SUS) and user feedback indicated several issues that made the website less user-friendly. This research aimed to develop design solutions (redesign) to address these user problems by employing a User-Centered Design (UCD) approach. Following implementation and subsequent SUS testing, the score improved significantly from 63.083 to 89.416. Furthermore, 5 usability components testing was conducted. The final results obtained were Learnability (89.5%), Memorability (91.7%), Efficiency (88.9%), Error (92%), and Satisfaction (92.9%) which increased from the previous results of Learnability (62.5%), Memorability (66%), Efficiency (62.7%), Error (74%), and Satisfaction (70%) These all indicating that the redesign successfully resolved the identified user issues.